Advancing Seismic Performance: Experimental Behavior of Hybridized Steel-FRP Composite Bars - Agamy, Mohamed H.; Gouda, Ahmed; Mostafa, Ibrahim T.; Nassar, Omar F.; EL Said Issa, Heba Mohamed; Ahmed, Ahmed M. (Civil Engineering Journal, 2025)
This study investigates the structural performance of reinforced concrete (RC) columns reinforced with hybrid Steel-FRP Composite Bars (SFCBs), offering a sustainable alternative to conventional steel and fiber-reinforced polymer (FRP) reinforcement. Eight large-scale RC columns, measuring 400 × 400 mm in cross-section and 1850 mm in height, were tested under combined cyclic and axial loading to simulate seismic conditions. The experimental variables included SFCB diameters (14 mm, 18 mm, 22 mm), axial load ratios (20%, 30%, 40%), and stirrup spacing (80 mm, 100 mm, 150 mm). The results indicate that SFCBs can effectively replace traditional steel reinforcement, providing comparable load-bearing capacity while significantly improving durability. Columns reinforced with SFCBs demonstrated superior initial stiffness and achieved higher drift ratios than steel-reinforced columns, exceeding the limits set by international design codes (ACI 440.2R, CSA S806-12, Eurocode 8) with maximum drift ratios of up to 6.5%. Increasing the SFCB diameter from 14 mm to 22 mm enhanced peak load capacity by 14%–20% and improved drift ratios by up to 113%. However, higher axial load ratios and wider stirrup spacing were found to reduce ductility. Specifically, increasing the axial load ratio from 20% to 40% decreased ductility by 13.46%, while increasing stirrup spacing from 80 mm to 150 mm reduced ductility by 8.90%. These findings underscore the potential of SFCBs to enhance the performance of RC columns in seismic and corrosive environments, offering a durable and sustainable solution for modern infrastructure. To the authors' knowledge, this study represents the first comprehensive investigation into the behavior of SFCB-reinforced RC columns under combined cyclic and axial loading, providing valuable insights for the design of resilient concrete structures.